Fabricating Graphene-Titanium ( - Tuğba Mutuk; Mevlüt Gürbüz (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2019)
Titanium has themost useful properties of the metal are corrosion resistancestrength-to-density ratio, the highest of any metallic element. In itsunalloyed condition, titanium is as strong as some steels but less dense. Due to its good features titanium can beused in the composite as a matrix material. Titanium matrix composites(TiMCs) can be used in various industries such as automotive, airplanes and especiallybiomaterials. Today, as carbon reinforcing material carbon nanotube (CNT),graphite and graphene are used as reinforcing materials. The graphene has themost remarkable properties in thisreinforced material due to its extraordinary mechanical features, low friction and high abrasion resistance. Compositematerials produced by using titanium and graphene may have remarkablemechanical and microstructural properties. Thisis conspicuous subject in recent years. In the present study, graphene(Gr) reinforced titanium composites wereproduced by powder metallurgy method. The effect of various percentagesof graphene (0-0,15-0,30-0,45-0,60 wt.%) on the microstructure, density,hardness and compressive strength of Ti composites have been investigated. From the mechanical tests after sintering at1100oC for 120min. The highest hardness and the greatest compressivestrength were obtained for 0,30 wt.% Gr reinforced composites (520.2 HV and 1137 MPa) when comparedto pure titanium (419.8 HV and 780 MPa). The crystal phase andmicrostructure of the composites were detectedby scanning electron microscopy (SEM) and X-ray diffractometer (XRD). Bettermechanical properties were observed for Ti-Gr composite materials when comparedpure Ti. These kinds of composites promise the future for using especially thefield of biomaterials.